2022
DOI: 10.1111/mam.12290
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting spatiotemporal behaviour in the European brown hareLepus europaeus: a meta‐analysis

Abstract: 1. The European brown hare Lepus europaeus is the most widely distributed hare species of the world, being naturally present throughout Eurasia and introduced as a game species in most continents. Despite the importance of this lagomorph for both management and conservation, a quantitative summary of its spatiotemporal behaviour is still lacking. 2. Taking advantage of 51 selected studies conducted throughout the native range of the hare and spanning the last 40 years, we used meta-analytic approaches in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…Throughout the year, the Eurasian beaver not only avoids diurnal hours, but also significantly reduces its activity on bright moonlight nights. This behaviour is adopted by some prey species [ 14 , 55 , 56 , 57 ] to limit encounters with their predators and with poachers. Where natural predators do not occur, the Eurasian beaver is mainly active on bright moonlight nights, allowing human avoidance, but with a foraging success improvement [ 33 ] since its vision is not well-adapted to movements in the dark.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the year, the Eurasian beaver not only avoids diurnal hours, but also significantly reduces its activity on bright moonlight nights. This behaviour is adopted by some prey species [ 14 , 55 , 56 , 57 ] to limit encounters with their predators and with poachers. Where natural predators do not occur, the Eurasian beaver is mainly active on bright moonlight nights, allowing human avoidance, but with a foraging success improvement [ 33 ] since its vision is not well-adapted to movements in the dark.…”
Section: Discussionmentioning
confidence: 99%
“…The arrival of new species (both native and introduced) in an area may locally disrupt this equilibrium, forcing new behavioural adaptations in coexisting species [ 7 , 13 ]. In turn, the alteration of spatiotemporal patterns of activity can increase species’ exposure to local threats, including predation and interspecific competition [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both European hares and rabbits were introduced to Sweden (Artdatabanken 2020). European hares are typically associated with agricultural lowland (Mori et al 2022), and their densities have been found to be positively correlated with higher temperatures and lower precipitation (Leach et al 2016;Smith et al 2005). While European hare populations have been declining in large parts of Europe since 1960 due to agricultural intensification (Smith et al 2005), they might still be expanding their distribution in Sweden (Jansson and Pehrson 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The European brown hare ( Lepus europaeus Pallas , 1778; hereafter hare) is the leporid with the widest global distribution [ 1 ]. Italian populations were significantly altered starting from the twentieth century by its restocking with captive-bred or allochthonous animals in order to maintain viable populations for hunting purposes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%